2000
DOI: 10.2343/geochemj.34.321
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal isotopic record of a Porites coral during the 1998 mass bleaching event.

Abstract: Based on skeletal oxygen and carbon isotope analyses, we found a remarkable decrease in skeletal linear extension rate of a Porites colony during the bleaching event of 1998 around the Ryukyu Islands. Water temperature in the summer of 1998 was recorded as the highest for at least last 50 years in the region. This colony, growing in a channel of fringing reef in Ishigaki Island, has experienced complete bleaching, as evidenced from direct observations of discoloration of the colony. Growth increment between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
5
22
0
Order By: Relevance
“…These calibrations were calculated using seasonal rather than monthly SSTs and δ 18 O c values. If seasonal averages are applied to our data, the calibration slope is -0.17 ‰/°C, in agreement with the Ishigaki calibrations (Abe et al 1998, Suzuki et al 1999.Models of δ 18 O fractionation in corals predict that as SST rises, δ18 O c will be depleted and the accreted skeleton will be isotopically lighter, and indeed, previous studies have reported depletion of δ 18 O c associated with extremely high SSTs that initiated bleaching events (Porter et al 1989, Leader et al 1991, Suzuki et al 2000. Surprisingly, however, the δ 18 O c record of colony S4 reveals enrichment of 0.3 ‰ between the summers of 1997 and 1998 rather than the expected depletion.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…These calibrations were calculated using seasonal rather than monthly SSTs and δ 18 O c values. If seasonal averages are applied to our data, the calibration slope is -0.17 ‰/°C, in agreement with the Ishigaki calibrations (Abe et al 1998, Suzuki et al 1999.Models of δ 18 O fractionation in corals predict that as SST rises, δ18 O c will be depleted and the accreted skeleton will be isotopically lighter, and indeed, previous studies have reported depletion of δ 18 O c associated with extremely high SSTs that initiated bleaching events (Porter et al 1989, Leader et al 1991, Suzuki et al 2000. Surprisingly, however, the δ 18 O c record of colony S4 reveals enrichment of 0.3 ‰ between the summers of 1997 and 1998 rather than the expected depletion.…”
supporting
confidence: 65%
“…18 O c will be depleted and the accreted skeleton will be isotopically lighter, and indeed, previous studies have reported depletion of δ 18 O c associated with extremely high SSTs that initiated bleaching events (Porter et al 1989, Leader et al 1991, Suzuki et al 2000. Surprisingly, however, the δ 18 O c record of colony S4 reveals enrichment of 0.3 ‰ between the summers of 1997 and 1998 rather than the expected depletion.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations